PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Desti Chintya Allufi; Nur Hidayati (JEM Jurnal Ekonomi dan Manajemen, 2020)
This study aims to examine the effect of capital structure as measured by the debt-to-equity ratio (DER), liquidity as measured by the current ratio (CR), and firm size as measured by the natural logarithm (Ln) of total assets on financial performance. as measured by return on equity (ROE) in textile and garment sub-sector companies for the 2015-2018 period. The sampling method used is purposive sampling. The sample used is 10 companies. The data analysis technique used is statistical analysis consisting of classical assumption test, multiple linear regression, coefficient of determination, and hypothesis testing using SPSS 22.0 software. The results showed that the capital structure (DER), liquidity (CR), and firm size simultaneously had a significant effect on financial performance (ROE). Partially, capital structure (DER), liquidity (CR), and firm size have a significant positive effect on financial performance (ROE).